2016
DOI: 10.1007/s12665-016-5466-z
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of PCE contaminated clay soil by coupling electrokinetics with zero-valent iron permeable reactive barrier

Abstract: In the present study, electrokinetic technology was coupled with a Permeable Reactive Barrier (PRB) composed of micro-scale Fe to treat a clay soil contaminated by Perchloroethylene (PCE) as a Dense Non-Aqueous Phase Liquid (DNAPL). A nonionic surfactant, Triton X-100, was selected as the solubility enhancing agent. A series of 10 d duration batch tests were carried out in order to evaluate the fate and transport and removal of PCE and to demonstrate the effectiveness of the non-uniform EK/ZVI PRB system for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…For example, reported that the insertion of Pd/Fe PRB caused EOF decrease 1.8 times in an electroremediation process for hexachlorobenzene-polluted soil. Kebria et al (2016) reported similar results in electroremediation of PCE polluted soil by using Fe 0 particles as PRB. On the other hand, same authors reported that coupling a Cu/Fe PRB in electroremediation of hexachlorobenzene-polluted soil caused that EOF increased.…”
Section: Field Code Changedsupporting
confidence: 58%
“…For example, reported that the insertion of Pd/Fe PRB caused EOF decrease 1.8 times in an electroremediation process for hexachlorobenzene-polluted soil. Kebria et al (2016) reported similar results in electroremediation of PCE polluted soil by using Fe 0 particles as PRB. On the other hand, same authors reported that coupling a Cu/Fe PRB in electroremediation of hexachlorobenzene-polluted soil caused that EOF increased.…”
Section: Field Code Changedsupporting
confidence: 58%
“…Wang et al [13] reported that a Pd/Fe PRB inclusion caused that EOF decreased 1.8 times in an electrokinetic remediation process of hexaclorobenzenepolluted soil. Kebria et al [14] reported similar results. On the contrary, the same authors [15] reported that a Cu/Fe PRB insertion caused that EOF increased, again in an electrokinetic remediation process of hexaclorobenzene-polluted soil.…”
Section: Resultsmentioning
confidence: 58%
“…Further, the pH variation in the cathode region was as follows: MEKC 6˃ MEKC 3˃ MEKC 5˃ MEKC 2˃ MEKC 1˃ MEKC 4. In the anode region, an acidic condition was established while the alkaline environment was produced in the cathode region; thus, pH increased in the cathode and decreased in the anode 52,53 . The fall in pH near the anode causes the cationic exchange of hydrogen with the contaminant absorbed on the sediment surface, leads to the release of the contaminant ions.…”
Section: Resultsmentioning
confidence: 99%